2008
DOI: 10.1088/0022-3727/41/19/195413
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature fast growth of nanocrystalline silicon films by rf-PECVD from SiH4/H2gases: microstructural characterization

Abstract: Hydrogenated nanocrystalline silicon thin films were deposited at a high rate of 0.8 nm s−1 by conventional (13.56 MHz) plasma enhanced chemical vapour deposition from SHi4/H2 gas mixture at a low temperature of 200 °C. The effects of hydrogen dilution, radio frequency power density, substrate temperature and deposition pressure on the crystalline volume fraction and the deposition rate of films were systematically investigated. The results show that the high hydrogen dilution and the substrate temperature are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…It is experimentally demonstrated that hydrogen content initially increases with the increase in dilution ratio (R) from 10 to 20, then drops abruptly in the R range of 20-30, and follows the gradually increasing hydrogen content as R values from 30 to 40. A previously reported hydrogen rich study indicated that an increase in RF power promotes the silane dissociation and produces more SiH x (x = 1, 2, 3) radicals [40] as well as the increased electron temperature [41]. In our study, RF power is set at 100 W, while the hydrogen dilution ratio (R) shows the similar impact such that the hydrogen rich precursors have higher sticking probability as the hydrogen content increases.…”
Section: Fourier Transform Infra-red (Ftir) Spectroscopy Analysismentioning
confidence: 79%
“…It is experimentally demonstrated that hydrogen content initially increases with the increase in dilution ratio (R) from 10 to 20, then drops abruptly in the R range of 20-30, and follows the gradually increasing hydrogen content as R values from 30 to 40. A previously reported hydrogen rich study indicated that an increase in RF power promotes the silane dissociation and produces more SiH x (x = 1, 2, 3) radicals [40] as well as the increased electron temperature [41]. In our study, RF power is set at 100 W, while the hydrogen dilution ratio (R) shows the similar impact such that the hydrogen rich precursors have higher sticking probability as the hydrogen content increases.…”
Section: Fourier Transform Infra-red (Ftir) Spectroscopy Analysismentioning
confidence: 79%
“…In view of this, low‐pressure, low‐frequency, thermally nonequilibrium, high‐density ICPs have shown to be an effective and versatile process to deposit high‐quality Si thin films at high rate. For example, Cheng et al demonstrated a very high growth rate of up to 2.4 nm S −1 for nanocrystalline Si:H films on Si(100) substrates from silane precursor gas without any hydrogen dilution using ICP‐CVD, compared to a few angstroms per second using conventional PECVD . Similarly, Si quantum dots embedded in an α‐SiC matrix obtained from the silane and methane gas mixture can be prepared by ICP‐CVD .…”
Section: Plasmas In Electrochemical Energy Conversion and Storage Matmentioning
confidence: 99%
“…In general, the nanocrystalline silicon thin lms are commonly synthesized by using plasma processing of precursor gases highly diluted in hydrogen that results in a low growth rate (typically, a few nm min À1 ). 21,[46][47][48] This severely retards the cost-effective production of nc-Si-based devices. Furthermore, although high hydrogen dilution indeed promotes nonepitaxial nanocrystalline growth, excessive hydrogenation leads to poor material performance (e.g., degradation upon light exposure, etc.)…”
Section: Photoluminescence Studiesmentioning
confidence: 99%